Fabrication of High‐Performance Palladium Supported on Activated Charcoal Nanocatalyst for Synthesis of Morphine Opioid Analgesics. Issue 14 (15th April 2020) - Nazari, Behzad; Mousavi, Sajjad; Keshavarz, Mohammad H.; Bordbar, Abdol‐Khalegh
Abstract: High‐performance palladium supported on activated charcoal (Pd/ACH ) is an important nanocatalyst for the synthesis of different types of opioid analgesics. In this work, the Pd/ACH nanocatalysts are fabricated by a suitable method using the chemical reduction with ethylene glycol (EG), 1‐propanol, ethanol, and methanol, which act as reducing, stabilizing, and dispersing agents. Since this method does not require surfactants and reducing agents that are hazardous to the environment and human health, it is an environmentally friendly method. The activity of produced nanocatalysts was determined by catalytic hydrogenation of 14‐hydroxynormorphinone to noroxymorphone because noroxymorphone is the key active metabolite of oxycodone, noroxycodone, and oxymorphone. Among catalysts, it is specified that nanocatalyst prepared by EG (Pd/ACHEG ) has the highest activity. The effect of the EG for increasing the rate of Pd reduction is related to its high boiling point, which results in a decrease in particle size. The results of the reusability of the Pd/ACHEG nanocatalyst show that the activity of nanocatalyst is reduced by 12 % after four runs. Fourier‐transform infrared (FTIR), inductively coupled plasma (ICP), transmission electron microscopy (TEM), x‐ray diffraction (XRD), Brunauer–Emmett–Teller (BET), x‐ray photoelectron spectroscopy (XPS), and H2 chemisorption analyses were used for the analysis of Pd/ACH nanocatalysts. Abstract : High‐performance Pd/ACH nanocatalyst was fabricated using the chemical reduction by ethylene glycol (EG), 1‐propanol, ethanol, and methanol that is an environmentally friendly method. The synthesis of morphine analgesics is one of the applications of this nanocatalyst. The hydrogenation of 14‐hydroxynormorphinone to noroxymorphone was used to measure the activity of the produced nanocatalysts. It was specified that nanocatalyst prepared by EG has the highest activity than to others. It has also reusability in several runs for the synthesis of morphine analgesics.